2011
DOI: 10.1007/s00403-011-1194-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of COX-2 activity and CRP levels in patients with non-melanoma skin cancer. −765G>C PTGS2 polymorphism and NMSC risk

Abstract: Non-melanoma skin cancer is one of the most common of all cancers and the incidence has increased in the last years as a result of many factors including increased tanning, life style and possible global climate change. Inflammation plays an important role in cancer development and is frequently evaluated by serum C-reactive protein (CRP) levels. PTGS2 -765C allele coding for COX-2 has been found to be associated with lower plasma levels of CRP. The objectives of this study are: evaluation of the association b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…It is well known that hereditary materials and environmental aspects could influence the risks and take a critical part in the tumorigenesis of numerous cancers [ 1 , 2 ], nevertheless, the risk attributable to each cancer is indistinct. Of them, an important one is AMP-activated protein kinase (AMPK).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that hereditary materials and environmental aspects could influence the risks and take a critical part in the tumorigenesis of numerous cancers [ 1 , 2 ], nevertheless, the risk attributable to each cancer is indistinct. Of them, an important one is AMP-activated protein kinase (AMPK).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that environmental factors and genetic predisposition may affect the individual's susceptibility and play an important role in the development of tumors (Cocos et al, 2012;Rubin et al, 2012;Arzumanyan et al, 2013;Hardbower et al, 2013), though the risk attributable to each is unclear. In recent years, a good many genes have been identified as potential digestive tract cancer susceptibility genes.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last decade, numerous molecular epidemiological case-control studies have been conducted in diverse ethnic backgrounds to explore the association between the COX2 -765G>C polymorphism and risks of various cancers, including breast cancer (Piranda et al, 2010), colorectal carcinoma (Daraei et al, 2012), esophageal (Bye et al, 2011) and gastric cancers , hepatocellular carcinoma (He et al, 2012), leukemia (Zheng et al, 2011), lung cancer (Coskunpinar et al, 2011), lymphoma (Monroy et al, 2011), ovarian (Agachan Cakmakoglu et al, 2011, head and neck (Peters et al, 2009), pancreatic (Zhao et al, 2009), skin (Cocoş et al, 2012), and cervical cancers (Pandey et al, 2010), among others. However, due to the relatively small sample sizes, the results obtained from these studies have been inconclusive or even controversial.…”
Section: Introductionmentioning
confidence: 99%